Asymmetric biotic interchange across the Bering land bridge between Eurasia and North America. Issue 4 (15th March 2019) - Jiang, Dechun; Klaus, Sebastian; Zhang, Ya-Ping; Hillis, David M; Li, Jia-Tang
ABSTRACT: The exchange of biotas between Eurasia and North America across the Bering land bridge had a major impact on ecosystems of both continents throughout the Cenozoic. This exchange has received particular attention regarding placental mammals dispersing into the Americas, including humans after the last glacial period, and also as an explanation for the disjunct distribution of related seed plants in eastern Asia and eastern North America. Here, we investigate bi-directional dispersal across the Bering land bridge from estimates of dispersal events based on time-calibrated phylogenies of a broad range of plant, fungus and animal taxa. We reveal a long-lasting phase of asymmetrical biotic interchange, with a peak of dispersal from Asia into North America during the late Oligocene warming (26–24 Ma), when dispersal in the opposite direction was greatly decreased. Influx from North America into Asia was lower than in the opposite direction throughout the Cenozoic, but with peak rates of dispersal at the end of the Eocene (40–34 Ma) and again in the early to middle Miocene (16–14 Ma). The strong association between dispersal patterns and environmental changes suggests that plants, fungi and animals have likely dispersed from stable to perturbed environments of North America and Eurasia throughout the Cenozoic.